Preparation of a 3D printable high-performance GelMA hydrogel loading with magnetic cobalt ferrite nanoparticles - Shi, Yiwan; Wang, Zhaozhen; Zhou, Xinting; Lin, Chengxiong; Chen, Chao; Gao, Botao; Xu, Weikang; Zheng, Xiaofei; Wu, Tingting; Wang, Huajun (Frontiers in Bioengineering and Biotechnology, 2023)
Osteosarcoma remains a worldwide concern due to the poor effectiveness of available therapies in the clinic. Therefore, it is necessary to find a safe and effective therapy to realize the complete resection of osteosarcoma and reconstruction of the bone defect. Magnetic hyperthermia based on magnetic nanoparticles can kill tumor cells by raising the temperature without causing the side effects of conventional cancer treatments. This research aims to design a high-performance magnetic hydrogel composed of gelatin methacrylate (GelMA) and highly magnetic cobalt ferrite (CFO) nanoparticles for osteosarcoma treatment. Specifically, CFO is surface functionalized with methacrylate groups (MeCFO). The surface modified CFO has good biocompatibility and stable solution dispersion ability. Afterward, MeCFO nanoparticles are incorporated into GelMA to fabricate a three-dimensional (3D) printable MeCFO/GelMA magnetic hydrogel and then photocross-linked by UV radiation. MeCFO/GelMA hydrogel has high porosity and swelling ability, indicating that the hydrogel possesses more space and good hydrophily for cell survival. The rheological results showed that the hydrogel has shear thinning property, which is suitable as a bioprinting ink to produce desired structures by a 3D printer. Furthermore, 50 μg/mL MeCFO not only decreases the cell activity of osteosarcoma cells but also promotes the osteogenic differentiation of mBMSCs. The results of the CCK-8 assay and live/dead staining showed that MeCFO/GelMA hydrogel had good cytocompatibility. These results indicated that MeCFO/GelMA hydrogel with potential antitumor and bone reconstruction functions is a promising therapeutic strategy after osteosarcoma resection.